COMPARATIVE ANALYSIS OF THE INFILTRATION MODEL IN AN URBAN CATCHMENT (PANGEEA, 2025)
As urbanization continues to expand due to decreasing of pervious area, there is a need to quantify its negative impacts on the hydrological level. The infiltration properties of the soils and the piezometric level have a direct impact on the hydrological behavior of urban catchments. The variety of these characteristics necessitates the use of appropriate infiltration models and should be included in urban hydrologic modeling. Hence, high accuracy models are a necessity in the management of the urban floods. This paper investigates the variability of the water depth on a urban catchment in Beilen (Netherlands) represented using the GIM. A 2D model was used to simulate the infiltration of water into the ground and model pluvial flows at an urban catchment scale. Water levels were satisfactorily simulated by the model. Comparative analysis reveals soil parameters are very sensitive.
Keywords: infiltration; hydrological modeling; urban catchments; drainage; floods